E EARNING MANAGEMENT: THE EFFECT OF MANAGEMENT OVERCONFIDENCE AND CORPORATE GOVERNANCE - Satria Tri Nanda; Raisya Zenita; Neneng Salimiah; Intan Adino (Jurnal Ilmiah Ekonomi Dan Bisnis, 2022)
Many studies have discussed the determinants of earning management. However, most of these studies discuss external factors of management such as audit quality and quality of disclosure and as a determinant of earning management. Study that tries to examine the intrinsic factors such as managerial overconfidence effect on earning management has not been widely conducted, especially in companies listed on IDX, Indonesia. This study aims to examine the effect of managerial overconfidence on earning management in companies listed on IDX. Furthermore, this study also aims to determine the moderating effect of corporate governance mechanisms on the relationship between managerial overconfidence. By using data analysis with the SEMPLS technique, the present study has succeeded to prove that managerial overconfidence affect earning management. Furthermore, this study also successfully provide evidence that corporate governance mechanisms such as independent audit committees and audit committee activities moderate the relationship between managerial overconfidence and earning management.